Impelementasi Framework Express JS Pada "Mupuk": Aplikasi Layanan Subsidi Pupuk Berbasis Android - Hamdan Ainur Riza Syakirin; Rr. Hajar Puji Sejati (JSAI (Journal Scientific and Applied Informatics), 2024)
In recent years, the development of information technology has changed various sectors, including the agricultural sector. One important policy in the agricultural sector is the fertilizer subsidy program, which aims to help farmers gain access to fertilizers at affordable prices and maintain food production stability. However, the challenge of distributing fertilizer subsidies in a targeted and efficient manner is still an issue that needs to be addressed. In developing this application, a backend framework that is fast, efficient, and capable of handling large amounts of data is required. Express.js is one framework that is widely used in the development of Node. js-based applications because of their reliability in building lightweight and fast APIs. This framework allows developers to build server-side applications that can support mobile applications in communicating data in real-time and effectively. Interpretation of Ease of Use results: 83% of users were satisfied or very satisfied, Interface design: 75% of users were satisfied with the interface design of the application, Speed of Response: 76% of users were satisfied with the application's response speed, Information Relevance: 88% of users felt that the information presented was very relevant, Overall Satisfaction: Overall, 81% of users were satisfied with the app, although some areas could be improved.